Perubahan Fiksasi Video Klip Musik : Problematika Hukum di Era Digital - Riki Dwi Putra; Dwi Suryahartati; Nelli Herlina (Zaaken: Journal of Civil and Business Law, 2020)
This article seeks to discuss how legal arrangement about fixation music video clip based on statutory regulation and whether changing a fixation on a music video clip is a valuation of the copyright perspective. This discussion is needed due to development of intellectual property rights are closely related with increasing intellecual abilities of humans. One of them is copyright where the basic idea of copyright is to protect the original form of human copyright works that were born because of their intellectual abilities. This article concludes that from law concerning copyright still lack of discussion about fixation and nothing legal protection for the creator of his creation especially on fixation music clip video. If viewed on from law concerning copyright there is nothing legal certainty is applied. The meaning of legal certainty is concerning applied on sanction for the violator who do change on fixation music video clip from someone else. The change of music video clip is including law violator based on copyright perspective because have been the work of copyright from someone else in this case is change background on music video cklip is result form label music copy right. Keyword: Fixation; Copyright; Music Video Clip. Abstrak Artikel ini membahas bagaimana pengaturan hukum mengenai fiksasi pada video klip musik berdasarkan perturan perundang-undangan dan apakah merubah fiksasi terhadap video klip musik merupakan pelanggaran dalam perspektif hak cipta. Pembahasan ini diperlukan karena perkembangan hak kekayaan intelektual erat kaitannya dengan semakin meningkatnya kemampuan intelektual manusia. Salah satunya dalam bidang hak cipta yang dimana ide dasar dari hak cipta adalah untuk melindungi wujud asli karya cipta manusia yang lahir karena kemampuan intelektualnya. Artikel ini menyimpulkan bahwa berdasarkan Undang-Undang Tentang Hak Cipta masih kurangnya pembahasan mengenai Fiksasi dan tidak adanya perlindungan hukum bagi pencipta atas ciptaannya terutama dalam bidang Fiksasi video klip musik. Jika dilihat dari Undang-Undang yang terbaru tentang hak cipta yaitu Undang-UndangTentang Hak Cipta tidak adanya kepastian hukum yang diterapkan. Kepastian hukum yang dimaksud adalah mengenai sanksi yang diterapkan bagi pelanggar yang melakukan perubahan terhadap Fiksasi video klip musik milik orang lain. Merubah Fiksasi video klip musik termasuk ke dalam pelanggaran hukum dalam perpektif hak cipta karna telah merubah hasil karya cipta orang lain dalam hal ini merubah latar belakang gambar video klip musik yang merupakan hasil dari karya cipta label musik. Kata Kunci: Fiksasi; Hak Cipta; Video Klip Musik.